Food security and food production systems - Porter, J.R.; Xie L; Challinor, Andrew J.; Cochrane, K.; Howden SM; Iqbal, M.M.; Lobell, David B.; Travasso, Maria (2014)
The effects of climate change on crop and terrestrial food production are evident in several regions of the world (high confidence). Negative impacts of climate trends have been more common than positive ones. Positive trends are evident in some highlatitude regions (high confidence). Since AR4, there have been several periods of rapid food and cereal price increases following climate extremes in key producing regions, indicating a sensitivity of current markets to climate extremes, among other factors. Several of these climate extremes were made more likely as the result of anthropogenic emissions (medium confidence).